Medical Ethics in Sports Investigating Legal Issues Surrounding Performance-Enhancing Drugs - David Kizito Ogwal (Uganda Christian University, 2024)
The use of performance enhancement drugs (PEDs) in sports poses multifaceted legal challenges at the intersection of athletic competition, health regulation, and ethical integrity. This abstract provides a comprehensive overview of the legal issues surrounding PEDs in sports, exploring the complex landscape of regulations, enforcement mechanisms, and ethical considerations. Central to the legal discourse is the tension between upholding the principles of fairness and integrity in sports and respecting athletes' rights to bodily autonomy and medical treatment. Regulatory bodies such as the World Anti-Doping Agency (WADA) play a pivotal role in establishing and enforcing anti-doping rules, conducting drug testing, and imposing sanctions on athletes found in violation. However, the efficacy and fairness of these regulations are subject to ongoing debate, with concerns raised about the consistency of enforcement, the impact on athletes' health, and the potential infringement of individual rights. Legal challenges in the realm of sports extend beyond anti-doping regulations to encompass issues of liability, contractual obligations, and athlete welfare. Athletes, coaches, and sports organizations grapple with questions surrounding the duty of care, informed consent, and the legal implications of performance-enhancing interventions. High-profile cases of doping scandals and legal disputes underscore the complexities of navigating the legal landscape while upholding the principles of justice and accountability.